Effects of photoluminescent pathways on the emergency evacuation behaviours of commuters in underground MRT stations - Chianh, Jia Xuan (Nanyang Technological University, 2021)
This study examined the effects of photoluminescent pathways on the emergency evacuation behaviours of commuters in underground MRT stations. Undergraduate students (N = 48) were tested on an MRT simulation game where they were tasked to find the exit as quickly as possible. All participants were allocated to the control condition (i.e., absence of photoluminescent pathways) and four experimental conditions (i.e., presence of photoluminescent pathways). The photoluminescent pathways in the experimental conditions differed on two characteristics: design (e.g., arrowed vs. non-arrowed) and location (floor-mounted vs. wall-mounted). It was predicted that the presence of photoluminescent pathways would improve the durations taken by the participants to find the MRT exit and the durations may differ by the characteristics of the photoluminescent pathways. It was found that participants took a shorter duration in the experimental conditions as compared to the control condition. Furthermore, the participants took the shortest duration in the experimental condition with the arrowed and floor-mounted photoluminescent pathways. However, they preferred the experimental condition with the arrowed and wall-mounted photoluminescent pathways instead, suggesting a possible combination of floor-mounted and wall-mounted arrowed photoluminescent pathways in future MRT stations.